Correlation Between Java Subdomain Proficiency and Java Information Technology Specialist (ITS) Certification Examination Success - Traballo, Roel Cortez (International Journal of Computing Sciences Research, 2025)
Purpose – This study explores the relationship between proficiency in Java subdomains and success in the ITS Certification Examination. By identifying which subdomain scores most strongly predict certification outcomes, this research provides insights to help enhance instruction and review programs for Java learners. Utilizing a dataset of 155 individuals, the study analyzed the relationship between scores in each subdomain and the final examination scores, determining pass/fail status based on a 70% passing threshold. Method – Using a correlational design, the study analyzed the scores of 155 students from five Java subdomains (Java Fundamentals; Data Types, Variables, and Expressions; Flow Control Implementation; Object-Oriented Programming; Code Compilation and Debugging) and their corresponding total ITS exam scores. Pearson’s correlation coefficient was calculated to determine the strength of correlation between subdomain performance and certification success. Result – All subdomains showed strong positive correlations with the ITS exam scores. Code Compilation and Debugging had the highest correlation (r = .987), followed by Flow Control Implementation (r = .944), Java Fundamentals (r = .940), and Object-Oriented Programming (r = .896). Conclusion – Mastery in Java subdomains, particularly in OOP and Exception Handling, is a significant predictor of ITS exam success. These findings highlight the need for enhanced emphasis on these topics in instruction and review programs. Recommendations – Educators must focus on project-based learning and continue core concept reinforcement in OOP and debugging. Certification authorities should frequently adjust the relative importance of the subdomains to keep the certification requirements up-to-date with industry ​‍​‌‍​‍‌trends. Research Implications – The findings contribute to the growing body of literature linking programming subdomain mastery to standardized assessment performance, supporting evidence-based instructional design. Practical Implications – The results can be used to refine academic curricula, enhance student review programs, and inform the development of competency-based learning interventions that align with certification standards.